Analisis Kesalahan Penggunaan Tanda Baca pada Berita Artikel Bangka Pos Edisi 2023 - Akhmad Rifqi Ramadhani; Rama Rosmanti; Puspa Indah Utami (Journal on Education, 2023)
In this study the important thing that was studied was about punctuation errors. Punctuation that serves to show the structure and order of words of a writing, and serves to regulate intonation, as well as pauses when reading. This study aims to: (1) describe the error of punctuation (.) On the news in the article Bangka.pos. (2) find out the punctuation error (,) on the news in the Bangka.pos article. (3) find out the punctuation error (-) on the news in the Bangka.pos article. the subject in this study was taken from data, namely news in the article Bangka. post. the objects in this study are a number of sentences that contain punctuation errors. In this particular research project, a documentation approach was used to obtain data for the research. The referential equivalent method is the approach taken to accomplish what needs to be done for this investigation.